(untitled) (Baghdad Science Journal, 2011)
In this work we fabrication holographic optical element diffraction grating thickness 40?m and mirror90?m by using dichromated gelatin,to perform that we have to use the Nd-yaG laser doubling frequency of wavelenght (532)nm and its powers of (80)mWatt.we have studyed the thickness and concentration dichromat effect in mirror reflaction ,effect of angle of reconstruction beam in band width and diffraction efficiency ,study effect gelatin hardener of the diffraction efficiency.